Preliminary risk management system for work-related fatigue among shift workers in the industrial context of Thailand: A review article - Chiamchunya, Arutchaporn; Sinthoppong, Kunakorn (Journal of Medical and Public Health Region 4, 2026)
Shift workers play a significant role in Thailand’s industrial development. However, shift work has been associated with various adverse health effects, particularly work-related fatigue. The literature indicates that work-related fatigue can be attributed to two main group of factors (1) individual factors, especially poor sleep quality, and (2) work-related factors, including shift schedules, workload intensity, and suboptimal working conditions. Work-related fatigue poses substantial risks in several areas. From a health standpoint, it contributes to circadian rhythm disturbances, increases vulnerability to non-communicable diseases, and is associated with mental health problems. In terms of occupational safety, fatigue increases the probability of workplace accidents. Additionally, it impairs work performance and reduces productivity. To address these concerns, Fatigue Risk Management System (FRMS) is proposed as a structured, evidence-based workplace intervention. Core components of an FRMS include workload management, shift design, employee educational programs, sleep disorder management, improvements to the work environment, and assessment of workers’ fitness for duty. Although the FRMS is not currently mandated under Thai occupational safety regulations, its implementation in the workplace is recommended. It offers a proactive approach to mitigating fatigue among shift workers, strengthens occupational health and safety standards, and enhances overall worker well-being in alignment with sustainable development goals.